E-062 Cerebral Aneurysm Debuting as Rupture during Diagnostic CT Angiography: An Unexpected Worst-case Scenario. (29th July 2016) - Dmytriw, A; Martinez Santos, J; Spears, J; Marotta, T
Abstract : Introduction: Rupture of a previously-asymptomatic intracranial aneurysm rupture is occasionally encountered during endovascular coiling, but is not considered a significant risk during invasive angiography and is seen rarely. 1 Acute rupture at the exact time of computed tomographicangiography (CTA) has not previously been reported, and intravenous contrast injection is not felt to be a risk factor for aneurysm rupture. Typically, CTA acquisition is not supervised by a physician, andidentification/reporting of acute phenomena by a radiographeris not currently standardized. We describe a case of rupture at the time of CTA, after which the patient experienced decompensation in an unsupervised waiting area. Case presentation: An asymptomatic 40 year-old woman was referred for evaluation of a left-sided unruptured carotid bifurcation aneurysm identified on workup for headaches. Upon returning from the CTA suite, she became progressively confused, and was immediatelytransferred to the emergency department. Rapid neurologicaldeterioration ensued, as her Glasgow coma scale dropped to 3 and her pupils became unreactive at 6 mm. The question of contrast allergy was initially raised. CTA revealed a previously-undetected posterior inferior cerebellar artery (PICA) aneurysm which demonstrated active contrast extravasation. She was urgently sedated, intubated, and infused with mannitol. A repeat unenhanced head CT showed a Fisher grade 4 subarachnoid hemorrhage with intraventricular extension and hydrocephalus, characteristic of ruptured PICA aneurysm. Bilateral external ventricular drains were placed, and a suboccipital craniectomy was performed expeditiously with successful haematoma evacuation and aneurysm clipping. She was transferredin stable condition to the neuro-intensive care unit, but unfortunately succumbed to vasospasm 10 days later. Discussion: This is the only case that has ever been observed in the careers of our staff of at our high-volume aneurysm center. The likelihood of this occurrence is certainly extraordinarily small. Nevertheless, high clinical suspicion is paramount for a fast, stepwise, and effective therapeutic response. The patient was unsupervised and it was only by chance that her deterioration was necessarily witnessed. In collaboration with out CT technologists, we held instituted in-services during which our staff were educated about ominous imaging findings and encouraged to emergently call a radiologist to confirm these. We propose that centers performing neuroimaging should at the very least be prepared to both supervise and initially manage patients who deteriorate. In addition, while many radiographers will inform an attending radiologist or another physician when an imaging finding appears concerning, standardization in the recognition and reporting of some acute pathological entities may improve detection and response in imaging departments. Disclosures: A. Dmytriw: None. J. Martinez Santos: None. J. Spears: None. T. Marotta: None.